The role of guidance and counselling services in addressing indiscipline among secondary school students in Nigeria - Lasisi, Adekola Kamil; Ibraheem, Islamiyyah Olajire (UIN Raden Mas Said Surakarta, 2023)
This study examines the correlation between guidance and counselling services and senior students' indiscipline in Ilorin South Local Government Area. The research utilized a correlational approach, collecting data through questionnaires distributed to 150 senior students in selected schools out of 67 secondary schools in Ilorin South LGA. The findings indicate a significant relationship between the availability and effectiveness of guidance and counselling services and the prevalence of indiscipline among senior students. The study revealed that there is a significant relationship between appraisal service and indiscipline among secondary school students in Ilorin South LGA. It also shows that there is a significant relationship between guidance counselling services and senior students’ indiscipline in Ilorin South LGA and there is a significant relationship between guidance information service and senior students’ indiscipline in Ilorin South L.G.A. The study highlights the importance of these support services in addressing indiscipline issues and emphasizes the need for their proper implementation to foster a disciplined and conducive learning environment. It was recommended that Raise awareness about the importance of guidance and counselling services and reduce any stigma associated with seeking help. Students should feel comfortable seeking assistance without fear of judgment or discrimination.